Comparison of Mono-Layer and Two-Layers Phantom Teeth Used in Preclinical Courses - I. Voborná; K. Foukalová; K. Francová (Czech Dental Chamber, 2014)
Introduction and aim of study: Preclinical practical exercises are an important part of teaching dentistry. It takes place on the phantom simulators, jaws and teeth in the adapted phantom labs. The aim of this experimental study was to assess the contribution of two-layer phantom teeth with carious lesions for teaching preclinical dentistry compared to mono-layer teeth without carious lesions. Material and methods: The study consisted of two parts - the questionnaire and a practical part. Questionnaires were surveyed students' opinions on various properties of mono-layer teeth without carious lesions (KaVo) with a two-layers tooth with carious lesions (Nissin). In the practical part the selected parameters of cavities were compared on both types of teeth. Results: 100 questionnaires were completed by all first-year students. Students were more satisfied with the two-layer teeth with carious lesions. Practical part were done by 88 first-year students. Each student made two fillings II. class according to Black, one on the mono-layer tooth and the second on the two-layers tooth. Some cavity parameters were better on two-layer teeth. Two-layer teeth with carious lesions were beneficial for preclinical practical exercises. Conclusion: Preclinical instruction and practical exercises on the phantom simulator and phantom teeth as most similar human jaw teeth are an important part of dental studies. Spatial orientation in dental tissues is an essential part of teaching. Experimental studies have shown that students are able to do better preparation on the two-layers teeth with carious lesions. These teeth also students in the questionnaire evaluated as more acceptable and suitable for preclinical teaching. The authors have same opinion.